Heparin-induced thrombocytopenia leading to stroke, lower extremity arterial occlusive disease, and skin necrosis: A case report. (March 2014) - Nazliel, B.; Batur Caglayan, H.Z.; Yildirim Capraz, I.; Irkec, C.; Yagci, M.; Gesoglu, T.
Abstract Enoxaparin sodium is a low molecular weight heparin (LMWH) used to treat and prevent deep venous thrombosis (DVT). The common complications related to the use of heparin are bleeding, allergic reaction, and osteoporosis. A less common complications are thrombocytopenia and thromboembolism that may not be generally recognized. We present a case of low molecular weight (LMW) heparin-induced thrombocytopenia (HIT) causing stroke, lower extremity arterial occlusion, and skin necrosis. Monitoring the platelet count is essential for early diagnosis of HIT. All patients who undergo heparinization should have a baseline platelet count done before the regimen is started and should be monitored closely especially during the first weeks of treatment.